Mind world : essays in phenomenology and ontology - Smith, David Woodruff, 1944- (Cambridge University Press, 2004)
"This collection explores the structure of consciousness and its place in the world, or inversely the structure of the world and the place of consciousness in it. Among the topics covered are the phenomenological aspects of experience (inner awareness, self-awareness), dependencies between experience and the world (the role of the body in experience, the role of culturally formed background ideas), and the basic ontological categories found in the world at large (unity, state-of-affairs, connectedness, dependence, and intentionality). Developing ideas drawn from historical figures such as Descartes, Husserl, Aristotle, and Whitehead, the essays together demonstrate the interdependence of ontology and phenomenology and its significance for the philosophy of the mind."--Jacket